The Evaluation Of Rock Brittleness Concept On Rotary Blast Hole Drills - R. Altindag (The Southern African Institute of Mining and Metallurgy, 2002)
The rock brittleness is one of the most important rock properties that affect the drill-ability of rocks. It is supposed that the increase in rock brittleness causes the increase in penetration rate. The drill-ability of rocks depends on many factors. These factors can be separated as two parts depending on a machine, bit type, rotational speed, thrust, blow frequency, flushing, and rock properties, brittleness, compressive strength, structure, hardness, etc. In this paper, the relationship between brittleness and drill-ability index, which is used in the prediction analysis of the penetration rate of rotary blast hole drills, were examined using regression analysis. It is also seen that significant correlations exist between brittleness and the drill-ability index.